CLINICAL PRESENTATION OF URINARY TRACT INFECTION AMONG CHILDREN AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Qureshi, Azhar Munir (Journal of Ayub Medical College Abbottabad, 2005)
Background: Urinary tract infection (UTI) is still common among children all over the world and a cause for significant number of out patient visits. Keeping in view the high incidence of UTI in children with associated morbidity and mortality, it is imperative to diagnose the urinary tract infection early and to treat the infection. We carried out this study to look into the clinical profile of UTI in children presenting at Ayub Teaching Hospital. Methods: One hundred patients of diagnosed UTI, from 0 to 15 years of age admitted in the Pediatric units of Ayub Teaching Hospital Abbottabad were included in the study. A proforma was used to record the clinical and laboratory presentation of these patients. Results: Fever was the commonest clinical presentation (92%) followed by dysuria (68%) and failure to thrive (31%). Conclusion: Clinical profile of urinary tract infection in children in this study was not significantly different from that of other developing and developed countries, however it will help us a lot in speedy diagnosis of our Paediatrics patients. Keywords: urinary tract infection, dysuria, failure to thrive, fever.